Pembentukan kelompok secara daring di Indonesia: Fenomena Sobat Ambyar - Mantara, Angga Yuni (Psikodinamika: Jurnal Literasi Psikologi, 2022)
Sobat Ambyar is a very interesting phenomenon considering that fan groups are usually formed from the start when an artist is famous. In contrast to other fan groups, ambyar friends appear when there is a special moment when one of the concert becomes viral on social media. In addition, Sobat Ambyar is an identity that is attached to a person, whether he is a member of the community or not. So, to see the differences and how individuals identify themselves as Sobat Ambyar and attach that identity to themselves, this research was carried out, especially the term Sobat Ambyar is an identity that emerges from social media and become social identity that emerged from online forum. The study used a phenomenological qualitative approach by conducting interviews with the initiator of Sobat Ambyar, the chairman of Sobat Ambyar Jakarta (SAJ), and the Commander of Sobat Ambyar. The results of the study indicate that the group initiation, values, member recognition, and structure are different, as well as several other things that are slightly different where SAJ has a more structured and well administered than the Sobat Ambyar group in Solo as the center. This is because the background and dynamics of the organization are also more complex.